Explorations between philosophy and history - Lorenz, Chris F.G. (Historein, 2013)
This introduction summarizes the basic ideas behind the articles collected in Przekraczanie granic: eseje z filozofii historii i teorii historiografii [Bordercrossings: essays on the philosophy of history and theory of historiography]. The first basic idea is the idea that the writing of history has a “border crossing” character, meaning that history writing involves border crossings, first, between history and philosophy and, second, between history and “politics” in a broad sense. The second basic idea is that the dialectical mechanism of “inversion” (of “negation” and of “the unity of opposites”) is fundamental for our understanding of debates in the philosophy of history and in historiography. The third idea is that interesting prejudices and other assumptions in both philosophy and in history are found by contrast, not by analysis (Feyerabend). Analysis of controversies is therefore the most fruitful point of departure in the philosophy of history and in historiography. Because all key ideas in the humanities are “essentially contested concepts” (Gallie), controversies are the “normal” discursive condition in the humanities.<!–[endif] –>